Three-dimensional biomechanical analysis of the stationary and penalty corner drives in field hockey - Whalen, M. T. (1992)
The purpose of this study was to describe the kinematics of the stationary drive and the penalty corner drive and determine anthropometric, temporal and technique variables most related to ball velocity by means of multiple regression analysis. Elite field hockey players (9 male, 8 female), over half of whom have had international playing experience, were analyzed by the use of three-dimensional video techniques. Three-dimensional coordinates were calculated by direct linear transformation (DLT). The greatest resultant ball velocity for the stationary drive was 32.64 m/s (average 26.44 m/s) and for the penalty corner drive 38.93 m/s (average 28.29 m/s). Both skills were described in terms of the movements which occurred at each joint as well as an analysis of the timing of phases and events throughout the skills. Anthropometric results indicated that subjects with greater biacromial breadth, greater forearm girth, greater mass and who were taller produced greater ball velocities.